2014
DOI: 10.1128/genomea.00116-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of a Bacillus anthracis Outbreak Strain from Zambia, 2011

Abstract: In August 2011, an anthrax outbreak occurred among Hippopotamus amphibius hippopotamuses and humans in Zambia. Here, we report the draft genome sequence of the Bacillus anthracis outbreak strain CZC5, isolated from tissues of H. amphibius hippopotamuses that had died in the outbreak area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In agreement with previous reports [ 8 , 17 , 19 , 33 ], the French isolates clustered into three canSNP types: A.Br.001/002 (branches located between canSNPs A.Br.001 and A.Br.002), A.Br.011/009 (branches located between canSNPs A.Br.009 and A.Br.011) and B.Br.CNEVA (branches beyond canSNP B.Br.004). The most basal node within group A is defined by the split of the A.Br.005/006 canSNP type represented by one strain from Cameroon [ 17 ] and seven from Zambia [ 34 , 35 ]. The Cameroon strain was previously shown to belong to MLVA cluster E described by Lista et al [ 36 ] corresponding to the "?"…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with previous reports [ 8 , 17 , 19 , 33 ], the French isolates clustered into three canSNP types: A.Br.001/002 (branches located between canSNPs A.Br.001 and A.Br.002), A.Br.011/009 (branches located between canSNPs A.Br.009 and A.Br.011) and B.Br.CNEVA (branches beyond canSNP B.Br.004). The most basal node within group A is defined by the split of the A.Br.005/006 canSNP type represented by one strain from Cameroon [ 17 ] and seven from Zambia [ 34 , 35 ]. The Cameroon strain was previously shown to belong to MLVA cluster E described by Lista et al [ 36 ] corresponding to the "?"…”
Section: Resultsmentioning
confidence: 99%
“…Anthrax is caused by Bacillus anthracis which is irregularly distributed worldwide in places where repeated outbreaks occur [2,3]. Outbreaks of Anthrax occur more frequently in developing countries like Ghana as compared to developed countries [4,5]. Rasko and colleagues in 2011 observed that there are 89 known strains of anthrax with the most widely recognized being the virulent Ames strain [6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the DNA was sequenced using the Ion Torrent PGM with fragment libraries, yielding a total of ~1,249,154,478 bp (coverage of 474 times). Assembly was performed with Mira 4.0.1 and Newbler 2.9 ( 15 ). We used CONTIGuator and FGAP 1.7 ( 16 ) to perform the alignment and gap closure steps, respectively.…”
Section: Genome Announcementmentioning
confidence: 99%